Occurence of pesticides in Dravsko polje aquifer - Anja Koroša; Nina Mali (Geologija, 2019)
The article presents the results of a research on the occurrence and concentration of pesticides in the groundwater of the Dravsko polje aquifer in the period from 2013 to 2015. Based on the results, the evaluation of spatial distribution of pesticides in groundwater and the relation to land use was performed. In different hydrogeological periods, 76 groundwater samples were collected at 19 different locations. 15 pesticides with their metabolites in groundwater were identified. Despite the prohibition of use, atrazine and its degradation product desethylatrazine still remain the most commonly detected pesticides in groundwater. They are followed by metolachlor, desethylterbutylazine and terbutylazine. The pesticides alachlor, dimetamide, metazachlor and terbutrin were not detected. The analysis of detected pesticides by land use indicates higher values in areas with intensive agricultural activity. In the northern part of the Dravsko polje, where the city of Maribor is located, pesticide concentrations are lower. Increased pesticide values occur in the southern part of the Dravsko polje, which coincides with more intensive agricultural land use of the area. The coefficient of degradation product / primary pesticide ratio (DAR and DTA/ TBA) was used to estimate the "age" of contamination from atrazine and terbutilazine. Surprising is the high incidence of atrazine, which may result from old burdens, slow decomposition and hydrogeological conditions, or the use of atrazine after the enactment of the ban